Analisis Pengaruh Kinerja Turbocharger pada Daya Mesin Induk Pada Kapal LPG/C Cipta Diamond - Robbi, Shofa Dai; Lao, Richard Imanuel Aldilenz; Darwis, Muhammad; Putri, Indah Ayu Johanda; Nugroho, Azis; Kristiyono, Antonius Edy (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Sea transportation is essential to global logistics, and the efficiency of a vessel’s propulsion system is critical to operational performance, especially on LPG carriers. Turbochargers enhance diesel engine volumetric efficiency by utilizing exhaust gases to compress intake air, enabling more complete combustion and greater power output. Declining turbocharger performance can reduce engine power, increase fuel consumption, and raise exhaust gas temperatures beyond safe limits. This study investigates the impact of turbocharger performance on the main engine power output of the LPG/C Cipta Diamond vessel. This study employs a descriptive qualitative approach, using data collection techniques such as direct observation, structured interviews with chief engineers and technicians, and documentation of engine logbook data. The collected data were analyzed using the Fishbone method (Ishikawa diagram) to identify the root causes of the observed decline in turbocharger performance. The findings indicate that several factors influence turbocharger performance, including the physical condition of its components, the cleanliness of the air intake ducts, exhaust gas temperature levels, and lubricant quality. Additionally, human factors and maintenance scheduling were found to significantly affect the stability of turbocharger performance. Mitigation measures implemented to address performance degradation include routine maintenance, examination of exhaust gas pressure and temperature, replacement of wear-prone components such as bearings and seals, and the use of air pressure and temperature monitoring systems to enable early detection of performance decline.